My Days in Prison - Iftikhar Gilani; GILANI (Iftikhar) (New Dehi Penguin Books, 2005)
A Shocking story of trial, temerity and triumph. On 9 June 2002, at 4.30 a.m., Iftikhar Gilani, a journalist with Kashmir Times, was roused from sleep by loud knocks at the door. Groggily he opened it to find a posse of policemen, some armed, carrying an authorization to search his house. Within minutes, they were turning his small flat inside out. Little did Gilani realize then that by the end of the day he would be in police custody. His supposed crime: providing information to Pakistans ISI (Inter Services Intelligence) on the deployment of armed forces in Jammu and Kashmir. The punishment: fourteen years in jail. My Days in Prison is Iftikhar Gilanis chilling account of the nightmare that followed. Overnight Gilani was turned from a career journalist to a confirmed spy. He was thrown into Tihar Jail and vilified in news reports. With his journalistic objectivity intact, Gilani narrates the horrors he was subjected to he was confined to the high-security ward, beaten till lie bled, made to clean filthy toilets with his shirt and then forced to wear the same shirt again . . . Eventually, in January 2003, the government withdrew the case in the wake of vociferous protests by civil rights activists and media personalities, and Gilani was a free man again. But his story demonstrates how important it is to uphold the rule of law and how easily an irresponsible few can misuse the draconian laws to their own ends. Most of all, he points out that, while he could prove his Innocence, the right to justice and personal liberty cannot be compromised in a democracy. As Gilani convincingly shows, this was not his fight alone.
Keywords: India; False imprisonment; Imprisonment; Journalists